Preventing and treating mange - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Symptoms and effects of mange, treatment by injection and dipping, housing and management, and the use of plants to treat mange.